"I feel safe here": Participants identify key components of syringe access programs. Issue 1 (2nd January 2022) - Ostrander, Noam; Carlberg-Racich, Suzanne
Abstract: Syringe access programs (SAPs) provide an array of supplies and services to people who inject drugs (PWID). Governmental reports within the United States have often neglected to include the voices of people who utilize SAPs. This project, which was part of a master's of public health practicum, surveyed 28 injection drug users about their experiences with an SAP in a major Midwestern city. Through this work, participants prioritized the supplies they most frequently need and the services they most often utilize. The results of this study may provide guidance to emerging SAPs that are working to prioritize supplies and services.